2007
DOI: 10.1152/ajpregu.00262.2007
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal immune challenge does not affect body weight regulation in rats

Abstract: The perinatal environment plays a crucial role in programming many aspects of adult physiology. Myriad stressors during pregnancy, from maternal immune challenge to nutritional deficiency, can alter longterm body weight set points of the offspring. In light of the increasing concern over body weight issues, such as obesity and anorexia, in modern societies and accumulating evidence that developmental stressors have long-lasting effects on other aspects of physiology (e.g., fever, pain), we explored the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 64 publications
6
27
0
1
Order By: Relevance
“…Importantly, the increase in the levels of these cytokines in the circulation was dissociated from the attenuated brain inflammation observed in our studies, and therefore negates their influence on the observed changes in neutrophil recruitment and favors the direct action of leptin on the brain as reported in this study. Interestingly, leptin levels were not affected by the LPS treatment in our experiments (Supplementary Table S1), in agreement with some 59,60 but contrary to other [16][17][18] studies. The reason for this apparent discrepancy is currently unclear, but the relatively late time point chosen in this study (24 h) may have not been ideal for the detection of LPS-induced leptin increase.…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, the increase in the levels of these cytokines in the circulation was dissociated from the attenuated brain inflammation observed in our studies, and therefore negates their influence on the observed changes in neutrophil recruitment and favors the direct action of leptin on the brain as reported in this study. Interestingly, leptin levels were not affected by the LPS treatment in our experiments (Supplementary Table S1), in agreement with some 59,60 but contrary to other [16][17][18] studies. The reason for this apparent discrepancy is currently unclear, but the relatively late time point chosen in this study (24 h) may have not been ideal for the detection of LPS-induced leptin increase.…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, P14 is a point in development where HPA axis responsiveness to stress begins to acquire an adult-like profile (50), potentially a vulnerable stage in the development of HPA axis function. In this regard, we have also observed, under some housing conditions, changes in adult body weight after an LPS challenge at P7 (82,83), an observation that has been replicated in rats treated at P10 (42). The hypothalamic pathways regulating body weight and metabolism are known to mature, in the rodent, between P6 and P12 (2, 13), making this a particularly sensitive time for these pathways.…”
Section: Unresolved Issuessupporting
confidence: 61%
“…This dose was chosen because it has been shown to induce behavioral and endocrine alterations and to increase cytokines at the placental level [12,13]. The estrous phase was chosen to standardize the female hormonal status.…”
Section: Methodsmentioning
confidence: 99%